Arthroscopic Rotator Cuff Repair Augmentation With Autologous Microfragmented Lipoaspirate Tissue Is Safe and Effectively Improves Short-term Clinical and Functional Results: A Prospective Randomized Controlled Trial With 24-Month Follow-up. Issue 5 (April 2022) - Randelli, Pietro S.; Cucchi, Davide; Fossati, Chiara; Boerci, Linda; Nocerino, Elisabetta; Ambrogi, Federico; Menon, Alessandra
Background: Autologous microfragmented lipoaspirate tissue has been recently introduced in orthopaedics as an easily available source of nonexpanded adipose-derived mesenchymal stem cells. Autologous microfragmented lipoaspirate tissue is expected to create a suitable microenvironment for tendon repair and regeneration. Rotator cuff tears show a high incidence of rerupture and represent an ideal target for nonexpanded mesenchymal stem cells. Purpose: To evaluate the safety and efficacy of autologous lipoaspirate tissue in arthroscopic rotator cuff repair. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: Consecutive patients referring to the investigation center for surgical treatment of magnetic resonance imaging–confirmed degenerative posterosuperior rotator cuff tears were assessed for eligibility. Those who were included were randomized to receive a single-row arthroscopic rotator cuff repair, followed by intraoperative injection of autologous microfragmented adipose tissue processed with an enzyme-free technology (treatment group) or not (control group). Clinical follow-up was conducted at 3, 6, 12, 18, and 24 months; at 18 months after surgery, magnetic resonance imaging of the operated shoulder was obtained to assess tendon integrity and rerupture rate. Results: An overall 177 patients were screened, and 44 (22 per group) completed the 24-month follow-up. A statistically significant difference in favor of the treatment group in terms of Constant-Murley score emerged at the primary endpoint at 6-month follow-up (mean ± SD; control group, 76.66 ± 10.77 points; treatment group, 82.78 ± 7.00 points; P = .0050). No significant differences in clinical outcome measures were encountered at any of the other follow-up points. No significant differences emerged between the groups in terms of rerupture rate, complication rate, and number of adverse events. Conclusion: This prospective randomized controlled trial demonstrated that the intraoperative injection of autologous microfragmented adipose tissue is safe and effective in improving short-term clinical and functional results after single-row arthroscopic rotator cuff repair. Registration: NCT02783352 (ClinicalTrials.gov identifier).